Early childhood education : an introduction - Seefeldt, Carol; Barbour, Nita. (Upper Saddle River, N.J. : Merrill, 1998)
Introducing early childhood education. Child growth and development. Individual differences: the effects of diversity. Relating with parents and other adults in school and community...
Keywords: Education; Early childhood education; Early childhood education -- United States